THE RECEPTION OF CHARLES DICKENS IN LITHUANIAN LITERARY CRITICISM (PART III) - Rudaitytė, Regina (Literatūra, 2012)
Although traditionally Dickens has always been regarded by Lithuanian critics and literary scholars as an emblematic English writer, one of the greatest representatives of the Victorian realist novel in England, his writing, however, has been given only cursory treatment in Lithuania, almost never until recently crossing the boundaries of biographical articles, reviews and notices with a biographical slant scattered in the press, particularly, but not only, during the early stages of reception. There is no book specifically dedicated to Dickens’s art by Lithuanian literary scholars, no comprehensive, fundamental and completely scholarly investigation of his writing. The critical assessment of Dickens’s writing has generally been coming in the form of reviews and articles dedicated to Dickens, in the form of prefaces and afterwords accompanying the translations of his books. In the inter-war years, Dickens was perceived as the great humanist, romanticist, and critic of the social evils of the Victorian England; he was glorified for his Christian ethics and his ‘Christmas philosophy’ with the focus on goodness and ‘religion of the heart’, with his cult of fireside tranquility. In the Soviet period, it is important to stress the tremendous influence of Marxist and communist ideology on the reception of Dickens who was favoured by the Marxist critics. In his writing they found the suitable object to dissect using the tools, whatever blunt, of the Marxist approach, which was the only possible method of literary analysis in Soviet times.Thus, during the period of Soviet occupation, Dickens was perceived as a typical representative of the social novel and of critical realism in English literature. His novels were popular because of political and social implications; he was the most translated and celebrated of English authors as providing a critique of capitalist society. This communist and Marxist bias was a crucial factor affecting the further reception of Dickens and putting many readers at large off his writing. Since the Soviet regime was abhorent to most people, they hated or at least looked with suspicion at everything that was praised and promoted in Soviet times.The epic character of Dickens’s novels, the social problems unfolded in them, realistic characterisation might have been a model for Lithuanian prose in the inter-war and in the Soviet periods; however, one would be hard pressed to trace direct influence of Dickens’s aesthetics on Lithuanian writers.Traditionally, Dickens is still highly regarded in the academic circles and his writing is the subject of seminars and lecture courses. Needless to say, in theory, Dickens, as a canonical writer, is on the shool reading-lists among other recommended writers and on the university curricula; practically, however, his writing is no longer popular today and is taught but sporadically. So what is Dickens today? Is there a new image of Dickens being shaped? For academics, he is still a great English writer of the Victorian Age and a great humanist; for general readers, he is now mostly associated with the issue of poverty and particularly with Christmas. For the last few years Dickens’s name cropped up in the Lithuanian press in connection with the approaching Christmas. However, no matter whether we speak about the so-called classic or the new, modernized image of Charles Dickens today, the scope of material devoted to his art and even recent translations of his works testify to his powerful presence in the popular Lithuanian imagination.